Innovating for women's, children's, and adolescents' health. (14th September 2015) - El-Noush, Haitham; Silver, Karlee L; Pamba, Allan O; Singer, Peter A
Abstract : Innovation is central to reaching the sustainable development goals on women's, children's, and adolescents' health. The task now is to scale up these innovations in a sustainable way, say Haitham El-Noush and colleagues